2007
DOI: 10.1007/s11258-006-9257-6
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to solar UV-B radiation accelerates mass and lignin loss of Larrea tridentata litter in the Sonoran Desert

Abstract: We assessed whether exposure to solar ultraviolet-B radiation (UV-B) affects the mass loss of Larrea tridentata (creosotebush) litter in the Sonoran Desert of central Arizona. We placed three types of litter (leaves, twigs, or a natural mixture of leaves, twigs, and seeds) in bags constructed of UV-B-transmitting or UV-Babsorbing filter material that allowed either 85% (near-ambient UV-B treatment) or 15% (reduced UV-B treatment) of the biologically effective solar UV-B to reach litter inside the bags. Bags we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
105
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(131 citation statements)
references
References 28 publications
23
105
2
1
Order By: Relevance
“…The presence of lignin is therefore actually predicted to protect cellulose from photodegradation, a phenomenon that has been documented to some extent and attributed to the strong light absorption of lignin and its high capacity for autoxidation (27,32). Our results support the idea that lignin was the primary loss product due to photodegradation in our standard substrates, and they are consistent with observations indicating the disappearance of lignin in litter exposed to high natural UV-B radiation (20) and increased biotic lability of plant litter after solar radiation exposure (21,26).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The presence of lignin is therefore actually predicted to protect cellulose from photodegradation, a phenomenon that has been documented to some extent and attributed to the strong light absorption of lignin and its high capacity for autoxidation (27,32). Our results support the idea that lignin was the primary loss product due to photodegradation in our standard substrates, and they are consistent with observations indicating the disappearance of lignin in litter exposed to high natural UV-B radiation (20) and increased biotic lability of plant litter after solar radiation exposure (21,26).…”
Section: Resultssupporting
confidence: 91%
“…Recent experimental evidence has shown that, in semiarid ecosystems, abiotic photodegradation can be a dominant control on decomposition of decaying plant material (18). Solar radiation causes mass loss from plant litter in low rainfall ecosystems (18)(19)(20)(21); photodegradation produces volatile carbon compounds (22)(23)(24) and alters the chemistry of the remaining material (21,25,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because ultraviolet irradiation accelerates organic matter decomposition, different wavelengths of ultraviolet light have been tested in practice (Moorhead and Reynolds 1989;Schade et al 1999;Day et al 2007;Brandt et al 2010). Due to its long wavelengths and ability to penetrate the ozonosphere, UV-A radiation (315 to 400 nm) has an important effect on photodecomposition in the biosphere .…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research has shown that degradation is affected by experimental conditions (time, environment, and location) and material properties (type and composition) (Schade et al 1999;Brandt et al 2007;Day et al 2007;Kirschbaum et al 2011). In general, when crop residue is exposed to increased UV radiation under dry conditions, the photodegradation of biomass materials is primarily driven by UV irradiation through direct or indirect photolysis.…”
Section: Introductionmentioning
confidence: 99%